Laminate and method for manufacturing the same
Patent Information
- Application Number
- JP2022093012
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-06-08
- Publication Date
- 2025-04-10
AI Technical Summary
Conventional thermally conductive materials used in LSI heat dissipation structures face challenges in achieving high thermal conductivity, particularly when silicon or similar materials are used, and there are issues with weight reduction, workability, and flexibility.
A laminate structure comprising a base material with metal-coated resin particles arranged at predetermined intervals, containing a curing component, curing agent, thermally conductive particles, and low-melting point metal particles, where the volume-average particle size ratio and arrangement optimize thermal conductivity.
The laminate achieves high thermal conductivity by enhancing the contact area and deformation of metal-coated resin particles, improving thermal conductivity even with materials like silicon, which are difficult to solder, and maintains reliability through alloy formation.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a laminate and a method for manufacturing a laminate. [Background technology]
[0002] In various electronic devices, such as LSIs (Large Scale Integrations), prolonged exposure to high temperatures due to heat generated by the components can lead to malfunctions or failures. Therefore, thermal conductive materials are widely used to prevent LSIs from overheating. These thermal conductive materials prevent overheating by diffusing the heat generated by the components or by transferring it to heat dissipation components that release it to the atmosphere or other external sources.
[0003] When metals or ceramics are used as such heat-conducting materials, problems arise such as difficulty in weight reduction, poor processability, or low flexibility. Therefore, various heat-conducting materials based on polymer materials such as resins or rubber have been proposed. For example, a heat-conducting adhesive has been proposed that includes a thermosetting adhesive containing a curing component and a curing agent for the curing component, and a metal filler dispersed in the thermosetting adhesive, wherein the metal filler consists of silver powder and solder powder, the solder powder exhibits a melting temperature lower than the thermosetting temperature of the heat-conducting adhesive, and reacts with the silver powder under the thermosetting conditions of the thermosetting adhesive to produce a high-melting-point solder alloy exhibiting a melting point higher than the melting temperature of the solder powder, the curing agent is a curing agent having flux activity toward the metal filler, the curing component is a glycidyl ether type epoxy resin, and the curing agent is a monoanhydride of tricarboxylic acid (see, for example, Patent Document 1). [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Patent No. 5796242 [Overview of the project] [Problems that the invention aims to solve]
[0005] However, in the prior art described in Patent Document 1 above, while the heat spreader in the heat dissipation structure can achieve high thermal conductivity through metal bonding, the heat-generating element (electronic component) in the heat dissipation structure is often made of silicon or the like, making it difficult to achieve high thermal conductivity through metal bonding.
[0006] The present invention aims to solve the aforementioned problems in the conventional era and achieve the following objectives. Specifically, the present invention aims to provide a laminate capable of achieving high thermal conductivity and a method for manufacturing the laminate. [Means for solving the problem]
[0007] The means to solve the aforementioned problem are as follows: <1> Substrate and The substrate contains metal-coated resin particles arranged at predetermined intervals, and also includes a heat-conducting layer containing a curing component, a curing agent for curing the curing component, heat-conducting particles, and low-melting-point metal particles. The metal-coated resin particles and the substrate are in contact, and the volume-average particle size of the metal-coated resin particles is smaller than the volume-average particle size of the heat-conducting particles. The laminate is characterized in that the substrate contains at least one selected from silicon, aluminum, tungsten, molybdenum, glass, mold resin, stainless steel, and ceramics. <2> The metal-coated resin particles and some of the heat-conducting particles contained in the heat-conducting layer are in contact with each other. <1> This is the laminate described in [reference]. <3> The ratio (A:B) of the volume-average particle size A of the metal-coated resin particles to the volume-average particle size B of the heat-conducting particles is 1:2 to 1:20. <1> from <2> It is a laminate described in any of the following. <4> The volume-average particle size of the metal-coated resin particles is 0.3 μm or more and 30 μm or less. <1> from <3> It is a laminate described in any of the following. <5> The volume-average particle size of the heat-conducting particles is 1 μm or more and 100 μm or less, <1> from <4> It is a laminate described in any of the following. <6> The metal-coated resin particles are at least one selected from gold-plated resin particles, silver-plated resin particles, copper-plated resin particles, and nickel-plated resin particles. <1> from <5> It is a laminate described in any of the following. <7> The heat-conducting particles are at least one of copper particles, silver-coated particles, and silver particles. <1> from <6> It is a laminate described in any of the following. <8> The low melting point metal particles include Sn and at least one selected from Bi, Ag, Cu, and In. <1> from <7> It is a laminate described in any of the following. <9> The curing component is at least one of an oxirane ring compound and an oxetane compound, <1> from <8> It is a laminate described in any of the following. <10> The thermal conductive layer has a counter substrate facing the substrate, The opposing substrate comprises at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof. <1> from <9> It is a laminate described in any of the following. <11> A thermal conductive layer formation step involves forming a thermal conductive layer on a substrate containing metal-coated resin particles arranged at predetermined intervals, and also containing a curing component, a curing agent for curing the curing component, thermal conductive particles, and low-melting-point metal particles. Includes, The method for manufacturing a laminate is characterized in that the substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, mold resin, stainless steel, and ceramics. [Effects of the Invention]
[0008] According to the present invention, it is possible to solve the aforementioned problems in the conventional method, achieve the aforementioned objectives, and provide a laminate and a method for manufacturing the laminate that can achieve high thermal conductivity. [Brief explanation of the drawing]
[0009] [Figure 1A] FIG. 1A is a schematic view showing an example of a laminate before pressure bonding according to the first embodiment. [Figure 1B] FIG. 1B is a schematic view showing an example of the laminate after pressure bonding according to the first embodiment. [Figure 2] FIG. 2 is a schematic cross-sectional view showing an example of the heat dissipation structure used in the present invention. [Figure 3] FIG. 3 is a cross-sectional SEM photograph at a location where the heat conduction layer and the base material in the laminate of Example 4 are in contact with each other.
MODE FOR CARRYING OUT THE INVENTION
[0010] (Laminate) The laminate of the present invention has a base material and a heat conduction layer containing metal-coated resin particles arranged at a predetermined interval and aligned, preferably has a counter base material, and further has other members as required.
[0011] In the present invention, a heat conduction layer containing metal-coated resin particles arranged at a predetermined interval and aligned is provided on the base material, the metal-coated resin particles and the base material are in contact with each other, the volume average particle diameter of the metal-coated resin particles is smaller than the volume average particle diameter of the heat conduction particles, and due to the increase in the contact area caused by the deformation of the metal-coated resin particles, even a base material with poor solder wettability composed of at least one selected from silicon, aluminum, tungsten, molybdenum, glass, mold resin, stainless steel, and ceramics can significantly improve the thermal conductivity.
[0012] (Base material) There are no particular restrictions on the shape, structure, size, material, etc. of the base material, and it can be appropriately selected according to the purpose. Examples of the shape of the base material include a plate shape and a sheet shape. Examples of the structure of the base material include a single-layer structure and a laminated structure. The size of the base material can be appropriately selected according to the application and the like. The material of the base material is a material that is difficult for solder to wet, and includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, mold resin, stainless steel, and ceramics. Examples of the ceramics include aluminum nitride, silicon carbide, alumina, gallium nitride, and the like. Examples of the mold resin include epoxy resin, silicone resin, urethane resin, acrylic resin, and the like. The average thickness of the base material is not particularly limited and can be appropriately selected according to the purpose. The base material may be the heat-generating body (electronic component) itself in the heat dissipation structure.
[0013] <Thermal conduction layer> The thermal conduction layer contains metal-coated resin particles arranged at a predetermined interval in an aligned state, and contains a curing component, a curing agent for curing the curing component, thermal conduction particles, and low melting point metal particles, and further contains other components as required.
[0014] -Curing component- As the curing component, it is preferable to use at least one of an oxirane ring compound and an oxetane compound.
[0015] --Oxirane ring compound-- The oxirane ring compound is a compound having an oxirane ring, and examples thereof include epoxy resin and the like. There is no particular limitation on the epoxy resin, and it can be appropriately selected according to the purpose. For example, glycidyl ether type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A type epoxy resin, trisphenol type epoxy resin, tetraphenol type epoxy resin, phenol-xylylene type epoxy resin, naphthol-xylylene type epoxy resin, phenol-naphthol type epoxy resin, phenol-dicyclopentadiene type epoxy resin, alicyclic epoxy resin, aliphatic epoxy resin, and the like can be mentioned. These may be used alone or in combination of two or more.
[0016] --Oxetane compounds-- The oxetane compound is a compound having an oxetanyl group, and may be an aliphatic compound, an alicyclic compound, or an aromatic compound. The oxetane compound may be a monofunctional oxetane compound having only one oxetanyl group, or a polyfunctional oxetane compound having two or more oxetanyl groups.
[0017] The oxetane compound is not particularly limited and can be appropriately selected depending on the purpose. Examples include 3,7-bis(3-oxetanyl)-5-oxa-nonane, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetanylmethoxy)methyl]propane, ethylene glycol bis(3-ethyl-3-oxetanylmethyl) ether, triethylene glycol bis(3-ethyl-3-oxetanylmethyl) ether, tetraethylene glycol bis(3-ethyl-3-oxetanylmethyl) ether, and 1,4 Examples include bis(3-ethyl-3-oxetanylmethoxy)butane, 1,6-bis(3-ethyl-3-oxetanylmethoxy)hexane, 3-ethyl-3-(phenoxy)methyl oxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-hydroxymethyl oxetane, 3-ethyl-3-(chloromethyl)oxetane, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, xylylenebisoxetane, and 4,4′-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP). These may be used individually or in combination of two or more.
[0018] As the oxetane compound, commercially available products can be used. Examples of such commercially available products include the "Aron Oxetane (registered trademark)" series sold by Toagosei Co., Ltd. and the "ETERNACOLL (registered trademark)" series sold by Ube Industries, Ltd.
[0019] Among the above oxirane ring compounds and oxetane compounds, glycidyl ether type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, phenol-dicyclopentadiene type epoxy resins, bisphenol A type epoxy resins, aliphatic epoxy resins, and 4,4′-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP) are preferred.
[0020] The content of the curing component is not particularly limited and can be appropriately selected depending on the purpose, but it is preferably 0.5% by mass or more and 60% by mass or less relative to the total amount of the first heat conductive layer.
[0021] -Hardening agent- The curing agent is a curing agent corresponding to the curing component, and examples include polyaddition curing agents such as acid anhydride-based curing agents, aliphatic amine-based curing agents, aromatic amine-based curing agents, phenol-based curing agents, and mercaptan-based curing agents, as well as catalytic curing agents such as imidazole. These may be used individually or in combination of two or more. Among these, acid anhydride-based curing agents are preferred. When the curing component is an epoxy resin, acid anhydride-based curing agents are preferred because they do not generate gas during thermal curing, can achieve a long pot life when mixed with an epoxy resin, and can achieve a good balance between the electrical, chemical, and mechanical properties of the resulting cured product. Examples of the acid anhydride-based curing agent include cyclohexane-1,2-dicarboxylic acid anhydride and monoacid anhydride of tricarboxylic acid. Examples of monoacid anhydride of tricarboxylic acid include cyclohexane-1,2,4-tricarboxylic acid-1,2-acid anhydride.
[0022] The curing agent is preferably one that has flux activity, as this improves the wettability of molten low-melting-point metal particles to heat-conducting particles. Methods for making the curing agent exhibit flux activity include, for example, introducing protic acid groups such as carboxyl groups, sulfonyl groups, and phosphate groups into the curing agent by known methods. Among these, introducing a carboxyl group is preferred from the viewpoint of reactivity with epoxy resin or oxetane compound as a curing component, and examples include organic acids containing carboxyl groups such as glutaric acid and succinic acid. Alternatively, it may be glutaric anhydride or a compound modified from succinic anhydride, or a metal salt of an organic acid such as silver glutarate.
[0023] The content of the curing agent is not particularly limited and can be appropriately selected depending on the purpose, but it is preferably 0.1% by mass or more and 30% by mass or less of the total amount of the heat conductive layer.
[0024] The molar equivalent ratio (C / D) of the curing component C and the curing agent D varies depending on the type of curing component and curing agent used and cannot be specified in general terms, but it is preferably 0.5 or more and 3 or less, more preferably 0.5 or more and 2 or less, and even more preferably 0.7 or more and 1.5 or less. When the equivalent ratio (C / D) is 0.5 or more and 3 or less, there is an advantage that the low-melting-point metal particles can sufficiently melt and form a network when the heat-conducting composition is thermally cured.
[0025] -Thermal Conducting Particles- The heat-conducting particles are preferably at least one of copper particles, silver-coated particles, and silver particles. Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles. There are no particular restrictions on the shape of the heat-conducting particles, and they can be appropriately selected depending on the purpose. Examples include spherical, flattened, granular, and needle-shaped particles. The volume-average particle size of the thermal conductive particles is preferably 1 μm or more and 100 μm or less, more preferably 10 μm or more and 70 μm or less, and even more preferably 10 μm or more and 50 μm or less. When the volume-average particle size of the thermal conductive particles is 1 μm or more and 100 μm or less, the volume ratio of the thermal conductive particles to the low-melting-point metal particles can be increased, thereby achieving high thermal conductivity. The aforementioned volume-average particle size can be measured, for example, using a laser diffraction / scattering particle size distribution analyzer (product name: Microtrac MT3300EXII).
[0026] -Low melting point metal particles- As the low-melting-point metal particles, solder particles specified in JIS Z3282-1999 are preferably used. Examples of the aforementioned solder particles include Sn-Pb solder particles, Pb-Sn-Sb solder particles, Sn-Sb solder particles, Sn-Pb-Bi solder particles, Sn-Bi solder particles, Sn-Bi-Ag solder particles, Sn-Cu solder particles, Sn-Pb-Cu solder particles, Sn-In solder particles, Sn-Ag solder particles, Sn-Pb-Ag solder particles, Pb-Ag solder particles, and Sn-Ag-Cu solder particles. These may be used individually or in combination of two or more types. Among these, solder particles containing Sn and at least one selected from Bi, Ag, Cu, and In are preferred, and Sn-Bi solder particles, Sn-Bi-Ag solder particles, Sn-Ag-Cu solder particles, and Sn-In solder particles are more preferred.
[0027] There are no particular restrictions on the shape of the low-melting-point metal particles, and they can be appropriately selected depending on the purpose. Examples include spherical, flattened, granular, and needle-shaped particles. The melting point of the low-melting-point metal particles is preferably 100°C or higher and 250°C or lower, and more preferably 120°C or higher and 200°C or lower. It is preferable that the melting point of the low-melting-point metal particles is lower than the thermosetting temperature of the thermal conductive composition, as this allows the molten low-melting-point metal particles in the cured product of the thermal conductive composition to form a network (continuous phase of metal) through the thermal conductive particles, thereby achieving high thermal conductivity. The low-melting-point metal particles react with the heat-conducting composition under the thermosetting treatment conditions to form an alloy with a higher melting point than the low-melting-point metal particles, thereby preventing melting at high temperatures and improving reliability. Furthermore, the heat resistance of the cured product of the heat-conducting composition is improved. The thermal curing treatment of the heat-conducting composition is carried out, for example, at a temperature of 150°C to 200°C for 30 minutes to 2 hours.
[0028] The volume-average particle size of the low-melting-point metal particles is preferably 10 μm or less, and more preferably 1 μm or more and 5 μm or less. When the volume-average particle size of the low-melting-point metal particles is 10 μm or less, the volume ratio of the low-melting-point metal particles to the heat-conducting particles can be reduced, thereby achieving high thermal conductivity. The volume-average particle size of the low-melting-point metal particles can be measured in the same manner as the volume-average particle size of the heat-conducting particles.
[0029] The volume-average particle size of the heat-conducting particles is larger than the volume-average particle size of the low-melting-point metal particles, and the volume-average particle size ratio (A / B) of the heat-conducting particles A to the low-melting-point metal particles B is preferably 2 or more, more preferably 3 or more, and even more preferably 5 or more. The upper limit of the volume-average particle size ratio (A / B) is preferably 20 or less, and more preferably 10 or less. By using low-melting-point metal particles with a volume-average particle size smaller than the aforementioned heat-conducting particles, the heat-conducting particles become the main component in the heat-conducting composition. The low-melting-point metal particles present between the heat-conducting particles melt upon heating and alloy with the heat-conducting particles to form a network, thereby achieving high thermal conductivity.
[0030] The volume ratio (A / B) of thermal conductive particles A to low-melting-point metal particles B in the thermal conductive layer is preferably 1 or more, more preferably 1.5 or more, and even more preferably 2 or more. The upper limit of the volume ratio (A / B) is preferably 5 or less, more preferably 4 or less, and even more preferably 3 or less. When the volume ratio (A / B) is 1 or greater, the volume proportion of heat-conducting particles, which have a larger volume-average particle size than low-melting-point metal particles, increases, thus suppressing the flow of molten low-melting-point metal particles. Furthermore, separation is less likely to occur even at interfaces that are difficult to wet (e.g., aluminum), thus reducing the influence of the interface material and improving the selectivity of the interface material.
[0031] -polymer- The thermal conductive layer preferably contains a polymer to provide flexibility and other properties. The polymer is not particularly limited and can be appropriately selected depending on the purpose. Examples include polymers having at least one structure selected from polybutadiene, polysiloxane, poly(meth)acrylate, polyalkylene, polyalkylene oxy, polyisoprene, polyisobutylene, polyamide, and polycarbonate structures within the molecule. The polymer content is preferably 1% by mass or more and 50% by mass or less, more preferably 1% by mass or more and 30% by mass or less, and even more preferably 1% by mass or more and 10% by mass or less, based on the total amount of the thermal conductive layer.
[0032] -Other ingredients- The thermal conductive layer may contain other components as long as they do not impair the effects of the present invention. The other components are not particularly limited and can be appropriately selected depending on the purpose. Examples include thermal conductive particles other than metals (e.g., aluminum nitride, alumina, carbon fiber, etc.) and additives (e.g., antioxidants, ultraviolet absorbers, curing accelerators, silane coupling agents, leveling agents, flame retardants, etc.).
[0033] In the present invention, the heat conductive layer includes metal-coated resin particles arranged at predetermined intervals. That is, the heat conductive layer has a particle alignment layer on the surface that is in contact with the substrate. It is preferable that the metal-coated resin particles and the substrate are in contact, and that the metal-coated resin particles and some of the heat-conducting particles contained in the heat-conducting layer are in contact. This makes it possible to achieve high thermal conductivity. The presence of metal-coated resin particles arranged at predetermined intervals on the surface of the thermal conductive layer that contacts the substrate can be easily confirmed with an optical microscope if the substrate is transparent to visible light, such as glass. If the substrate is transparent to infrared light, such as silicon, it can be observed using an infrared microscope. In addition, if the substrate is mold resin or ceramics, it can be observed using an X-ray microscope.
[0034] -Metal coated resin particles- The metal-coated resin particles are preferably resin particles with high thermal conductivity and relatively soft properties. Examples include gold-plated resin particles, silver-plated resin particles, copper-plated resin particles, and nickel-plated resin particles. These may be used individually or in combination of two or more. Among these, gold-plated resin particles are preferred from the viewpoint of thermal conductivity and stability. Examples of materials for the resin particles include divinylbenzene polymer, polystyrene resin, epoxy resin, phenolic resin, acrylic resin, acrylonitrile styrene (AS) resin, and benzoguanamine resin. These may be used individually or in combination of two or more. The volume-average particle size of the metal-coated resin particles is preferably 0.3 μm or more and 30 μm or less, and more preferably 0.5 μm or more and 10 μm or less. The volume-average particle size of the metal-coated resin particles can be measured in the same manner as the volume-average particle size of the heat-conducting particles.
[0035] Preferably, at least a portion of the metal-coated resin particles are exposed from the heat-conducting layer. This allows the metal-coated resin particles to deform when the laminate is pressed together, causing the binder component to melt and reach the substrate surface, thereby improving adhesion to the heat-conducting layer.
[0036] Preferably, the metal-coated resin particles are arranged in a regular pattern that repeats a predetermined arrangement when viewed in plan view of the heat-conducting layer. For example, the arrangement of the metal-coated resin particles can be a square lattice arrangement when viewed in plan view of the heat-conducting layer. Other forms of regular arrangement of metal-coated resin particles include lattice arrangements such as rectangular lattices, orthorhombic lattices, hexagonal lattices, and triangular lattices. The arrangement of metal-coated resin particles may also be a combination of multiple lattices of different shapes. As a form of arrangement of metal-coated resin particles, rows of particles arranged linearly at predetermined intervals may be placed in parallel at predetermined intervals. Regions in which the metal-coated resin particles are densely arranged and regions in which they are sparsely arranged may be regularly repeated. It is preferable for the metal-coated resin particles to be individually independent and spaced apart from one another in order to improve heat conductivity. Furthermore, the arrangement also includes a configuration in which multiple metal-coated resin particles are linked or closely spaced to form a unit, and these units are regularly arranged. When the metal-coated resin particles are arranged in a regular pattern, the grid axis or arrangement axis of the arrangement may be parallel to or intersect with at least one of the longitudinal direction of the heat-conducting layer and the direction perpendicular to the longitudinal direction.
[0037] There are no particular restrictions on the interparticle distance of metal-coated resin particles, and they can be appropriately selected depending on the purpose. For example, the nearest neighbor particle distance is preferably 0.5 times or more the volume-average particle size of the metal-coated resin particles, and more preferably 0.7 times or more. On the other hand, the nearest neighbor particle distance is preferably 100 times or less the volume-average particle size of the metal-coated resin particles, and more preferably 50 times or less.
[0038] The number density of metal-coated resin particles is 100 particles / mm³. 2 The above is preferable, with 300 pieces / mm 2 More than 70,000 pieces / mm 2 The following is more preferable: 6,000 pieces / mm2 More than 45,000 pieces / mm 2 The following is even more preferable.
[0039] The average thickness of the thermal conductive layer is not particularly limited and can be appropriately selected depending on the purpose, but it is preferably 0.1 μm or more and 100 μm or less, and more preferably 1 μm or more and 30 μm or less.
[0040] <Opposite substrate> The opposing substrate is positioned opposite the substrate, and there are no particular restrictions on its shape, structure, size, material, etc., and it can be appropriately selected according to the purpose. Examples of the shape of the opposing substrate include plate-like and sheet-like shapes. Examples of the structure of the opposing substrate include single-layer and laminated structures. The size of the opposing substrate can be appropriately selected depending on the application. The material of the opposing substrate is a material that is easily wetted by solder and includes at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof. The average thickness of the opposing substrate is not particularly limited and can be appropriately selected depending on the purpose. The opposing substrate may be the heat spreader itself in the heat dissipation structure.
[0041] <Other components> Other components are not particularly limited and can be selected as appropriate depending on the purpose, such as intermediate layers and protective layers.
[0042] (Method of manufacturing a laminate) The present invention's method for manufacturing a laminate includes a step of forming a heat conductive layer, and further includes other steps as necessary.
[0043] <Thermal Conduction Layer Formation Process> The aforementioned heat conductive layer formation step is a step of forming a heat conductive layer on a substrate that contains metal-coated resin particles arranged at predetermined intervals, and also contains a curing component, a curing agent for curing the curing component, heat conductive particles, and low-melting-point metal particles. The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, mold resin, stainless steel, and ceramics. The metal-coated resin particles are the same as the metal-coated resin particles contained in the heat-conducting layer, so their description is omitted. Furthermore, the curing component, curing agent, first heat-conducting particles, and low-melting-point metal particles are the same as the curing component, curing agent, first heat-conducting particles, and low-melting-point metal particles contained in the heat-conducting layer, so their description is omitted.
[0044] As a method for forming a heat conductive layer containing the metal-coated resin particles arranged at predetermined intervals, for example, a mold is prepared in which recesses corresponding to the arrangement pattern of the metal-coated resin particles are formed, the metal-coated resin particles are filled into the recesses of the mold, and a heat conductive layer containing a curing component formed on a release film, a curing agent for curing the curing component, heat conductive particles, and low-melting-point metal particles is bonded on top of the metal-coated resin particles and pressed in. By doing so, a heat conductive film can be formed in which the metal-coated resin particles are arranged at predetermined intervals by transferring the metal-coated resin particles to the heat conductive layer in a predetermined pattern. If necessary, this heat conductive film may have a two-layer structure by bonding an insulating adhesive layer supported by a release film to the metal-coated resin particle arrangement layer. By arranging a heat-conducting film on a substrate so that it is in contact with metal-coated resin particles and then pressing it down, a heat-conducting layer can be formed in which the metal-coated resin particles are aligned and separated at predetermined intervals.
[0045] The aforementioned heat-conducting film can be manufactured, for example, by applying a heat-conducting composition containing a curing component, a curing agent for curing the curing component, heat-conducting particles, and low-melting-point metal particles onto a release film and curing it. Methods for applying the heat-conducting composition onto the release film include, for example, inkjet method, blade coating method, gravure coating method, gravure offset coating method, bar coating method, roll coating method, knife coating method, air knife coating method, comma coating method, U-comma coating method, AKKU coating method, smoothing coating method, microgravure coating method, reverse roll coating method, 4-roll coating method, 5-roll coating method, dip coating method, curtain coating method, slide coating method, and die coating method.
[0046] <Other processes> Other processes are not particularly restricted and can be selected as appropriate depending on the purpose.
[0047] Herein, embodiments of the laminate of the present invention will be described in detail with reference to the drawings. In each drawing, the same reference numerals are used for the same components, and redundant descriptions may be omitted. Furthermore, the number, position, shape, etc. of the components described below are not limited to this embodiment, and may be set to a number, position, shape, etc. that is preferable for carrying out the present invention.
[0048] <First Embodiment> Figure 1A is a schematic diagram showing an example of a laminate before compression according to the first embodiment. The laminate 10 in Figure 1 contains a base material 11, metal-coated resin particles 15 arranged at predetermined intervals, and a thermal conductive layer 13 containing a curing component, a curing agent for curing the curing component, thermal conductive particles, and low-melting-point metal particles, and a counter base material 14 on the thermal conductive layer 13. The metal-coated resin particles 15 and the substrate 11 are in contact, and the volume-average particle size of the metal-coated resin particles is smaller than the volume-average particle size of the heat-conducting particles. Preferably, at least a portion of the metal-coated resin particles 15 are exposed from the heat-conducting layer 13. Figure 1B is a schematic diagram showing an example of a laminate before compression according to the first embodiment. When the laminate is compressed, the metal-coated resin particles 15 deform, and the binder component in the heat-conducting layer melts and reaches the surface of the substrate, improving the adhesion between the substrate 15 and the heat-conducting layer 13.
[0049] The laminate of the present invention can be suitably used when constructing a power LED module or power IC module by bonding a thermal interface material (TIM), an LED chip, or an IC chip mounted on a heat dissipation substrate to a heat sink, which fills the minute gap between a heat source such as an LSI and a heat sink, thereby allowing heat to flow smoothly between them. Here, power LED modules come in wire-bonded and flip-chip mounting types, while power IC modules come in wire-bonded mounting types.
[0050] The heat dissipation structure used in the present invention is composed of a heat-generating element, a laminate of the present invention, and a heat dissipation member.
[0051] There are no particular restrictions on the heat-generating element, and it can be appropriately selected according to the purpose. Examples include electronic components such as CPUs (Central Processing Units), MPUs (Micro Processing Units), and GPUs (Graphics Processing Units).
[0052] The heat dissipation member is not particularly limited as long as it is a structure that dissipates the heat generated by electronic components (heat-generating elements), and can be appropriately selected according to the purpose. Examples include heat spreaders, heat sinks, vapor chambers, and heat pipes. The heat spreader is a component for efficiently transferring heat from the electronic component to other components. There are no particular restrictions on the material of the heat spreader, and it can be appropriately selected according to the purpose, for example, copper, aluminum, etc. The heat spreader is usually in the shape of a flat plate. The heat sink is a component for releasing heat from the electronic component into the air. There are no particular restrictions on the material of the heat sink, and it can be appropriately selected depending on the purpose, for example, copper, aluminum, etc. The heat sink has, for example, a plurality of fins. The heat sink has, for example, a base portion and a plurality of fins provided so as to extend in a direction non-parallel to one surface of the base portion (for example, in a direction perpendicular to it). The heat spreader and the heat sink generally have a solid structure with no internal space. The vapor chamber is a hollow structure. A volatile liquid is sealed inside the hollow structure. Examples of the vapor chamber include a hollow heat spreader, a hollow heat sink, or a plate-shaped hollow structure. The heat pipe is a hollow structure that is cylindrical, substantially cylindrical, or flattened. A volatile liquid is sealed inside the hollow structure.
[0053] Here, Figure 2 is a schematic cross-sectional view showing an example of a semiconductor device as a heat dissipation structure. The laminate 7 of the present invention dissipates heat generated by electronic components 3 such as semiconductor elements, and as shown in Figure 2, it is fixed to the main surface 2a of the heat spreader 2 that faces the electronic components 3, and is sandwiched between the electronic components 3 and the heat spreader 2. In addition, the thermal conductive sheet 1 is sandwiched between the heat spreader 2 and the heat sink 5.
[0054] The heat spreader 2 is formed, for example, in the shape of a rectangular plate and has a main surface 2a facing the electronic component 3 and side walls 2b erected along the outer circumference of the main surface 2a. The heat spreader 2 has a thermal conductive sheet 1 provided on the main surface 2a surrounded by the side walls 2b, and a heat sink 5 is provided on the other surface 2c opposite to the main surface 2a via the thermal conductive sheet 1. The higher the thermal conductivity of the heat spreader 2, the lower the thermal resistance and the more efficiently it absorbs heat from electronic components 3 such as semiconductor elements. For example, it can be formed using copper or aluminum, which have good thermal conductivity.
[0055] The electronic component 3 is, for example, a semiconductor element such as a BGA, and is mounted on the wiring board 6. The heat spreader 2 also has the leading edge of its side wall 2b mounted on the wiring board 6, thereby surrounding the electronic component 3 at a predetermined distance by the side wall 2b. Furthermore, by providing the laminated body 7 of the present invention on the main surface 2a of the heat spreader 2, a heat dissipation member is formed that absorbs the heat generated by the electronic component 3 and dissipates heat from the heat sink 5. [Examples]
[0056] The following describes embodiments of the present invention, but the present invention is not limited in any way to these embodiments.
[0057] (Example 1) <Preparation of thermal conductive composition> The composition and content of each component listed in Example 1 of Table 1 were uniformly mixed using a stirring device (Awatori Rentaro Automatic Revolving Mixer, manufactured by Thinky Co., Ltd.) to prepare the heat conductive composition of Example 1. The content of each component in Table 1 is in parts by mass.
[0058] <Fabrication of thermal conductive film> The thermal conductive composition of Example 1 was applied to a release film (PET38GS, manufactured by Lintec Corporation) by bar coating, heated at 80°C for 15 minutes, and dried to produce a thermal conductive film with an average thickness of 100 μm.
[0059] <Preparation of a film-like master disc in which metal-coated resin particles are aligned> First, the master plate used in the example was prepared as follows: A 2 mm thick nickel plate was prepared, and cylindrical protrusions (outer diameter 4 μm, height 4 μm, center-to-center distance 6 μm) were formed in a hexagonal grid pattern over a 50 cm square area of the plate, with a surface density of 32,000 protrusions / mm². 2 This was used as the master disc for the transfer. Next, a polyethylene terephthalate (PET) substrate film with a width of 50 cm and a thickness of 50 μm was prepared. A photocurable resin composition containing 100 parts by mass of acrylate resin (M208, manufactured by Toagosei Co., Ltd.) and 2 parts by mass of a photopolymerization initiator (IRGACURE184, manufactured by BASF Japan Ltd.) was applied to this PET substrate film to a film thickness of 30 μm. The obtained photocurable resin composition film is pressed with a nickel transfer disc from its convex surface, and a high-pressure mercury lamp (1,000 mJ / cm²) is applied. 2 By irradiating the PET substrate film with light, a photocurable resin layer was formed in which the convex portions of the transfer disc were transferred as concave portions. By continuously repeating this operation while aligning it along the longitudinal direction of the PET substrate film, a film-like master disc of approximately 10 m was obtained in which the convex portions of the transfer disc were transferred as concave portions. The obtained film-like master disc had concave portions arranged in a hexagonal grid pattern, corresponding to the convex portion pattern of the transfer disc. Next, gold-plated resin particles 1 (manufactured by Sekisui Chemical Co., Ltd., AUL703, volume average particle size 3 μm) were prepared as metal-coated resin particles, and these gold-plated resin particles were scattered multiple times on the surface of a film-like master disc. Then, the gold-plated resin particles were wiped with a cloth to fill the recesses of the film-like master disc, which had been cut to a length of 30 cm. Here, in order to ensure that there were gold-plated resin particles that were not filled into this resin mold, the number of gold-plated resin particles scattered or the number of times they were scattered was adjusted to obtain areas in which the gold-plated resin particles were in a predetermined state of absence.
[0060] <Transfer of gold-plated resin particles onto a heat-conducting film> Next, the heat-conductive film was placed on a cut film-like master disc filled with gold-plated resin particles under predetermined conditions, with the length of the film matching the length of the film and the width including the central part of the film-like master disc. The metal-plated resin particles were then transferred by pressing at 60°C and 0.5 MPa. The insulating resin layer film was then peeled off from the film-like master disc, and the aligned metal-plated resin particles on the heat-conductive film were pressed into the heat-conductive film by applying pressure (pressure conditions: 60°C to 70°C, 0.5 MPa). This process was repeated at five points on the cut film-like master disc to produce a heat-conductive film in which the gold-plated resin particles were embedded in an aligned state.
[0061] <Fabrication of laminates> A thermal conductive film, in which gold-plated resin particles are embedded in an aligned manner, was placed between a 30mm x 30mm x 2mm base material (silicone) and a 30mm x 30mm x 2mm opposing base material (copper), with the gold-plated resin particles in contact with the base material. This was then heated at 150°C for 60 minutes to cure, thereby producing the laminate of Example 1.
[0062] (Example 2) The laminate of Example 2 was prepared in the same manner as in Example 1, except that the gold-plated resin particles 1 (manufactured by Sekisui Chemical Co., Ltd., AUL703, volume-average particle size 3 μm) were replaced with nickel-plated resin particles (manufactured by Sekisui Chemical Co., Ltd., Micropearl Ni-plated product, volume-average particle size 3 μm).
[0063] (Example 3) The laminate of Example 3 was prepared in the same manner as in Example 1, except that gold-plated resin particle 1 (manufactured by Sekisui Chemical Co., Ltd., AUL703, volume-average particle size 3 μm) was replaced with gold-plated resin particle 2 (manufactured by Nippon Chemical Industrial Co., Ltd., Bright 26GNR series, volume-average particle size 3 μm).
[0064] (Example 4) The laminate of Example 4 was prepared in the same manner as in Example 1, except that the gold-plated resin particles 1 (manufactured by Sekisui Chemical Co., Ltd., AUL703, volume-average particle size 3 μm) were replaced with silver-plated resin particles (manufactured by Mitsubishi Materials Electronic Chemicals, Ltd., Silver Coated Powder Series, volume-average particle size 3 μm). Figure 3 shows a cross-sectional SEM image of the laminate of Example 4 at the point where the thermal conductive layer and the substrate are in contact. From Figure 3, it can be seen that silver-plated resin particles are arranged at predetermined intervals on the surface where the thermal conductive layer and the substrate are in contact.
[0065] (Comparative Example 1) A laminate of Comparative Example 1 was prepared in the same manner as in Example 1, except that the gold-plated resin particles (Sekisui Chemical Co., Ltd., AUL703, volume-average particle size 3 μm) were replaced with resin particles without metal plating (Sekisui Chemical Co., Ltd., Micropearl SP, volume-average particle size 3 μm).
[0066] (Comparative Example 2) A laminate of Comparative Example 2 was prepared in the same manner as in Example 1, except that the gold-plated resin particles were not transferred to the heat-conducting film.
[0067] (Comparative Example 3) In Example 1, a thermal conductive composition described in Comparative Example 3 in Table 2 was prepared, and a thermal conductive film formed using the thermal conductive composition was used to create the laminate of Comparative Example 3, in the same manner as in Example 1.
[0068] Next, the thermal conductivity of each resulting laminate was evaluated as follows. The results are shown in Tables 1 and 2.
[0069] <Thermal conductivity> For each resulting laminate, the thermal resistance (°C·cm) was measured using a method compliant with ASTM-D5470. 2 The thermal resistance (W / m·K) was measured. From the results, the thermal resistance of the base material and the opposing base material was subtracted to calculate the thermal resistance of the cured product. From the thermal resistance and the thickness of the cured product, the thermal conductivity (W / m·K) was determined, and the thermal conductivity was evaluated according to the following criteria. [Evaluation Criteria] ◎: Thermal conductivity is 20 W / m·K or higher 〇: Thermal conductivity is 10 W / m·K or higher and less than 20 W / m·K ×: Thermal conductivity is less than 10 W / m·K
[0070]
Table 1
[0071]
Table 2
[0072] Details of each component in Tables 1 to 2 are as follows.
[0073] - Curing Component - * OXBP: Manufactured by Ube Industries, Ltd., 4,4′-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl
[0074] - Curing Agent - * Polycarboxylic Acid: Synthetic product of Dexerials Co., Ltd.
[0075] - Low Melting Point Metal Particles (Solder Particles) - * Sn 58 Bi 42 : Manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size Dv: 4 μm, melting point 139 °C
[0076] - Thermal Conductive Particles - * Thermal Conductive Particle 1: Ag-coated Cu particles, manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size Dv: 40 μm * Thermal Conductive Particle 2: Ag particles: manufactured by DOWA Electronics Co., Ltd., volume average particle size Dv: 1 μm
[0077] - Alignment Particles - * Gold-plated Resin Particles 1: Manufactured by Sekisui Chemical Co., Ltd., AUL703, volume average particle size 3 μm *Gold-plated resin particles 2: Manufactured by Nippon Chemical Industrial Co., Ltd., Bright 26GNR series, volume-average particle size Dv: 3μm *Nickel-plated resin particles: Manufactured by Sekisui Chemical Co., Ltd., Micropearl Ni-plated product, volume average particle size 3μm *Silver-plated resin particles: Manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd., silver-coated powder series, volume-average particle size 3μm *Resin particles without metal plating: Micropearl SP, manufactured by Sekisui Chemical Co., Ltd., volume average particle size 3μm
[0078] -polymer- *M1276: Polyamide compound manufactured by Arkema Corporation. [Industrial applicability]
[0079] The laminate of the present invention can achieve high thermal conductivity as a thermal interface material (TIM), and is therefore suitable for use around various electrical devices such as CPUs, MPUs, power transistors, LEDs, and laser diodes, where temperature can adversely affect the efficiency and lifespan of the element's operation. [Explanation of Symbols]
[0080] 1. Thermal conductive sheet 2 Heat spreader 2a Main surface 3. Heat-generating element (electronic component) 3a Top side 5 Heatsink 6 Wiring board 7 Laminate 10 Laminate 11 Base material 13. Thermal conductive layer 14 Opposing substrate 15 Metal-coated resin particles 16 Heat-conducting particles
Claims
1. A substrate; a thermally conductive layer on the substrate, the thermally conductive layer including metal-coated resin particles spaced apart from one another and aligned at a predetermined interval, a curing component, a curing agent for curing the curing component, thermally conductive particles, and low-melting-point metal particles; the metal-coated resin particles are in contact with the substrate, and the volume average particle size of the metal-coated resin particles is smaller than the volume average particle size of the thermally conductive particles; A laminate, wherein the substrate comprises at least one material selected from the group consisting of silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.
2. The laminate according to claim 1 , wherein the metal-coated resin particles are in contact with some of the thermally conductive particles contained in the thermally conductive layer.
3. 3. The laminate according to claim 1, wherein the ratio (A:B) of the volume average particle size A of the metal-coated resin particles to the volume average particle size B of the thermally conductive particles is 1:2 to 1:
20.
4. 3. The laminate according to claim 1, wherein the volume average particle diameter of the metal-coated resin particles is 0.3 μm or more and 30 μm or less.
5. 3. The laminate according to claim 1, wherein the thermally conductive particles have a volume average particle size of 1 μm or more and 100 μm or less.
6. 3. The laminate according to claim 1, wherein the metal-coated resin particles are at least one selected from the group consisting of gold-plated resin particles, silver-plated resin particles, copper-plated resin particles, and nickel-plated resin particles.
7. The laminate according to claim 1 , wherein the thermally conductive particles are at least one of copper particles, silver-coated particles, and silver particles.
8. The laminate according to claim 1 , wherein the low-melting-point metal particles contain Sn and at least one selected from the group consisting of Bi, Ag, Cu, and In.
9. The laminate according to claim 1 , wherein the curing component is at least one of an oxirane ring compound and an oxetane compound.
10. a facing substrate on the thermally conductive layer facing the substrate; 3. The laminate according to claim 1, wherein the opposing substrate comprises at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof.
11. a thermally conductive layer forming step of forming a thermally conductive layer on a substrate, the thermally conductive layer including metal-coated resin particles aligned at a predetermined interval, a curing component, a curing agent for curing the curing component, thermally conductive particles, and low-melting-point metal particles; Including, 10. A method for producing a laminate, wherein the substrate comprises at least one material selected from the group consisting of silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.